The Idea of Inclusivism As A New Era of Islamic Education - Khozinul Alim; Rachma Sulastri (Symfonia: Jurnal Pendidikan Agama Islam, 2024)
The theme of this paper is inclusivism as a new era of Islamic education, and the purpose of this study is to prove that inclusivism is the solution to Islamic education facing educational problems. Both dichotomies of knowledge, exclusivism and the form of teaching that does not teach students. For this reason, this study is normative philosophical, exploring and reading Islamic education books to be further analysed through an intellectual, substantial approach. The description presented is descriptive and supported by authoritative sources. This study concludes the importance of the new paradigm of Islamic education, which includes creating inclusive education by changing from Teaching to Learning so that Islamic education can develop its potential and learn to solve all life problems or with the term learning how to learn (learn how to learn) and this is the new era of Islamic education.